Pengujian UI / UX Game Genshin Impact Menggunakan Cognitive Walkthrough - Sudaryanto, Aris; Oskash Ivaldy, Amsyar Raftan; Nurindiyani, Artiarini Kusuma; Safrodin, Mohamad (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
Games as a medium of entertainment have taken root in society, even now games are starting to shift to become an alternative learning medium. One of the games that has many players in Indonesia is Genshin Impact, which is a role-playing game (RPG) genre. Genshin Impact is a combination of action and RPG games that combine open world elements. Genshin Impact has interesting graphics and storylines, but the success factor of a game is not only graphics and storylines, but also good UI/UX design. The design of the user interface (UI) must carefully consider human psychology and physiology factors, considering factors such as color, shape, and gameplay layout that can affect the quality of UI/UX. This study focuses on testing the UI/UX of the Genshin Impact game using the cognitive walkthrough (CW) method. Based on test data from 20 respondents, it was found that in general Genshin Impact has a good UI UX, but has shortcomings related to the use of icons, including icons that do not match player expectations, icons that confuse players, and the absence of information on the icon.